Revisiting the Pedicled Gastrocnemius Flap for Orthoplastic Limb Reconstruction - Mohd Yusof, Nazri; Ahmad Alwi, Akmal Azim (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Gastrocnemius muscle flap is performed in a combined approach of the orthopaedic and plastic team for limb reconstruction in the developed countries. However, this practice is not readily available in Malaysia because of the smaller numbers of plastic surgery services in government hospitals. This study reviews the outcome of the gastrocnemius flap performed by the orthopaedic team. MATERIALS AND METHODS: Thirty-two patients underwent gastrocnemius flap surgery with a mean age of 35.3 years (range 13-82). The flaps were done to cover the upper third (22), upper half (4), knee (2), distal femur (2) and the popliteal fossa (1). The initial problems were open fracture (21), infection following plating (5), necrotising fasciitis (3), degloving injury (1), pin site infection (1) and melioidosis (1). Five patients were having underlying Diabetes mellitus, 3 Hepatitis B, 2 HIV and 1 Hepatitis C infections. RESULTS: There was no flap necrosis. Complications include persistence infection in 3 patients which required advancement of the flap (1) and additional fasciocutaneous flap (2) to cover the wound breakdown. All fractures achieved union but one patient with infection following double plating for tibial plateau fracture developed chronic osteomyelitis. One patient develops transient peroneal nerve palsy following the lateral gastrocnemius transfer. Both patients who had patella ligament reconstruction with gastrocnemius flap develop knee stiffness. CONCLUSIONS: Gastrocnemius flap is a reliable and safe procedure in salvaging the leg from amputation related to open fractures and infections in orthopaedic surgery. It should be one of the options for the operative procedure taught during the orthopaedic training.